Développement De Module D'auto Apprentissage Sur PPT Pour Les Cours Français Écrit Introductif Basé Sur Powerpoint (Program Studi Pendidikan Bahasa Prancis, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2022)
Modules are defined as subject matter that is compiled and presented in writing in such a way that the readers are expected to be able to absorb the material themselves. Learning modules can be used in independent and group learning. In learning French, students learn skills which consist of four aspects, namely reading, speaking and writing skills. The development of PPT-based individual learning modules has the potential to be realized to support Français Ecrit Introductif learning. The aims of this study are (1) to describe the needs of first semester students of French Education Study Program of UNNES for power point-based media in Français Ecrit Introductive learning, (2) to describe the forms of power point-based media to support individual learning. This research method is Research and Development (R&D). Research and Development (R&D) Methods: there are ten research steps. However, this study only used five steps. namely formulating potentials and problems, collecting data, making product designs, validating designs, and revising designs. These five steps were used to create a powerpoint-based individual learning module for Français Ecrit Introdutif. The results of this study are based on the researcher's analytical questionnaire regarding the need for a powerpoint-based individual learning module in the Français Ecrit Introdutif course.The powerpoint-based individual learning module contains practice questions about shopping and daily activities and answer keys. The powerpoint-based self-learning module contains practice questions about shopping and daily activities and the answer key in the powerpoint-based self-learning module in Français Ecrit Introductif.